Atrial Fibrillation as an Initial Presentation of Thyroid Storm Newly Known Case in Elderly: Case Report - Vanny Hilda Fabiola; Chandra Wijaya; Yurnisa Fauziah (Universitas Ibn Khaldun Bogor, 2026)
Introduction: Atrial fibrillation as an initial presenting symptom of thyroid storm especially in underdiagnosed hyperthyroidism’s patient is still under-reported in the literature. Thyroid storm is an uncontrolled hyperthyroid condition caused by an extreme increase in thyroid hormone in the circulation which is a rare life-threatening clinical condition. Atrial fibrillation can occur in 2 out of 10 thyroid storm patients with a mortality rate up to 25% if left untreated. Case Illustration: A 73-year-old woman, came to the ER at Awal Bros A Yani Hospital with palpitation as a chief complaint. The patient had never experienced in this complaint before, never been diagnosed with thyroid nodules or grave’s disease or ongoing any treatment. Patient was done treated aggressive and intensively as initial management in Intensive Care Unit (ICU) and continued with management of thyroid storm by controlling the tachyarrhythmia and underlying etiology disease. The examination tools were physical and laboratory examination tools. The data analysis technique used descriptive analysis with the result total score of Wayne Index Criterial is 30 (hypoerthyroidism) and using the Burch-Wartofsky criteria, with total Burch-Wartofsky Point Scale (BPWS) score is 60 suggestive of Thyroid Storm. Physical examination found a lump in the left side anterior neck area approximately 3x3 cm. On ECG examination, a picture of atrial fibrillation was obtained. From laboratory examination, it was found that there was a decrease in TSHS < 0.05 uIU/ml and an increased FT4 5.65 pmol/L and X-ray showed cardiomegaly with signs of pulmonary congestion. Conclusion: Early detection of thyroid storm can prevent mortality and morbidity because it is often missed due to atypical symptoms. Providing treatment for underlying conditions can reduce patient morbidity and mortality.